Carl Bouchard - Hakim, Mona (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary Carl Bouchard's self-portraits are fictitious, emotional mise en scènes, in which the laying bare of the body corresponds to the laying bare of feelings. Bouchard is a multi-disciplinary artist, and his works draw upon performance, photography, and installation. More than a simple propensity to maintain a gaze on oneself, his transgressive images of needy people demand affection as an aptitude for commitment, authenticity, self-surrender. More precisely, they deal with the responsibility borne by each individual for how we look at others.